Implementation of Project-Based Learning model on Local Wisdom in Number Theory - Istiqomah Istiqomah (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
The purpose of the study was to describe the application of project-based learning based on local wisdom in the Number Theory course. The subjects of this study were students of the Mathematics Education Study Program, FKIP UST, who took the Number Theory course in the even semester of the 2020/2021 Academic Year, totaling 40 students. The instruments used in this study were in the form of project report documents and interview guidelines. The project report document contains the report title, project design, activity schedule, project implementation (tools, materials, and product manufacturing steps), project results (presenting the steps for using the product made). Project appraisal includes planning, preparation, data processing, data presentation, reports, and presentations. While the interview guide is in the form of student responses regarding project-based learning which includes messages, impressions, input, and suggestions. The analysis technique used is the descriptive qualitative analysis technique. The results of data analysis provide information that 100% of students can make project planning well, 58.62% of students can prepare for project implementation well, 79.31% of students do data processing well, 72.41% of students can present data well, 96.55% were able to make reports well, and 55.17% were able to present project results very well. Students are very interested in this local wisdom-based media creation project because they are directly involved in media making, so they gain valuable experience in preparing and presenting project results. These media are not only useful for explaining number theory material, especially GCD and LCM materials, through this media students also learn to preserve traditional games that are almost extinct.